Characterization of CD8 T Cell-Mediated Mutations in the Immunodominant Epitope GP33-41 of Lymphocytic Choriomeningitis Virus - Smyth, Mark; Khamina, Kseniya; Popa, Alexandra; Gudipati, Venugopal; Agerer, Benedikt; Lercher, Alexander; Kosack, Lindsay; Endler, Lukas; Baazim, Hatoon; Viczenczova, Csilla; Huppa, Johannes B.; Bergthaler, Andreas (Frontiers in Immunology, 2021)
Cytotoxic T lymphocytes (CTLs) represent key immune effectors of the host response against chronic viruses. In response to this selection pressure, viruses may accumulate escape mutations that evade CTL-mediated control. To study the emergence of CTL escape mutations, we employed the murine chronic infection model of lymphocytic choriomeningitis virus (LCMV). We developed an amplicon-based next-generation sequencing pipeline to detect low frequency mutations in the viral genome and identified non-synonymous mutations in the immunodominant LCMV CTL epitope, GP33-41, in infected wildtype mice. Infected Rag2-deficient mice lacking T and B cells did not contain such viral mutations. By using transgenic mice with T cell receptors specific to GP33-41, we characterized the emergence of viral mutations in the GP33-41 epitope under varying selection pressure. We investigated the two most abundant viral mutations by employing reverse genetically engineered viral mutants encoding the respective mutations. These experiments provided evidence that these mutations prevent activation and expansion of epitope-specific CD8 T cells. These findings on the mutational dynamics of viral escape mutations in a widely-studied viral CTL epitope contributes to our understanding of how chronic viruses interact with their host and evade the immune response. This may guide the development of future treatments and vaccines against chronic infections.